FOR THE TREATMENT OF PATIENTS WITH ATROPHIC NAZOPHARINGITIS, THE USE OF POLYMER-BASED OINTMENTS (World Bulletin of Public Health, 2024)
This article discusses the treatment of atrophic nazopharyngitis. The study involved 43 patients aged from 8 to 72 years, and upon admission a general clinical examination, radiography of the paranasal sinuses and a study of excretory function were performed. Introduction and the base of medicinal preparations such as riboflavin and glucose, along with this, it is ground in a dry form in a mortar, then the rest of the base is gradually added with part of the prepared base, mixed and heated in a water bath until riboflavin is dissolved and a uniformly colored mass is obtained. Thus, clinical observations indicate significant advantages of the polymer base used for the preparation of medicinal ointments that are used for atrophic nazopharyngitis
Keywords: atrophic nasopharyngitis; carboxymethylcellulose; ribovlavin